2012
DOI: 10.31384/jisrmsse/2012.10.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Status of Women in Pakistan: A Critical Analysis

Abstract: The status of women in Pakistan is worsening day by day and their living standard is also decreasing abysmally. Women in Pakistan do not only suffer from domestic inequalities in terms of the distribution of resources but their access to outside resources like education and employment is minimal and support from government or non-governmental organizations is nominal. Patriarchal structures embodied in kinship, religion, division of labour, violence and class hierarchy have further reinforced subordination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 12 publications
0
36
0
1
Order By: Relevance
“…They concluded that that the subordination and exclusion of Pakistani women in the development activities, flows from the barrel of patriarchy, which has denied women the right of choice in engaging themselves either in productive and reproductive activities. Under the patriarchal ideology, women's labor has been divided into productive and reproductive spheres (Isran & Isran, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that that the subordination and exclusion of Pakistani women in the development activities, flows from the barrel of patriarchy, which has denied women the right of choice in engaging themselves either in productive and reproductive activities. Under the patriarchal ideology, women's labor has been divided into productive and reproductive spheres (Isran & Isran, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On occasion, he would enter the baby's room, make a loud command, and the rest of the family would immediately leave, including his own mother. Whether a marriage is consanguineous or not, in traditional societies a family line continues through the birth of a healthy male son [7,15]. Mrs. A's brother demanded that the staff "fix the baby," with the explanation that he needed to be saved "because he is the first born male."…”
Section: Miscommunication and Mixed Messagesmentioning
confidence: 99%
“…women only have access to the only type of labour power they can control, and to old-age security, through their married sons. Since sons are a woman's most critical resource, ensuring their life-long loyalty is an enduring pre-occupation" [15]. If Mrs. A. returns to her home country, it is uncertain whether her husband's family will accept her.…”
Section: Miscommunication and Mixed Messagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Women in specific become victims of these patriarchal prejudices and suffer from physical, psychological and social violence at the hands of men (Tarar & Pulla, 2014). Such violence originates from the power practices of emotional and physical control of husbands over wives, fathers over daughters and brothers over sisters, shaping women for the roles and social functions defined by men in society (Cixous, 1986;Walby, 1990;Isran & Isran, 2012). The problems become even worst for women when they internalize these roles and synchronize them with their performative roles, thereby finding it natural to be oppressed (Butler, 1988).…”
Section: Introductionmentioning
confidence: 99%